112 Shunt Survival Benefit Associated With Complete vs Partial Revision. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Stone, Jonathan Jay; Walker, Corey; Jain, Minal; Jacobson, Maxwell; Phillips, Valerie; Silberstein, Howard J.
Abstract: INTRODUCTION: The placement of a cerebrospinal fluid shunt is an effective treatment for hydrocephalus, but the failure rate remains high. There is an unclear association between the shunt components that are modified during revision and subsequent failure rate. METHODS: A retrospective analysis was performed using a pediatric shunt database from 1990 to 2010. Patient demographics, shunt equipment used, and cause of shunt failure were compared with component revised by χ 2 analysis. Complete revisions were listed if an entirely new shunt system was implanted and partial if a subtotal revision was performed. Kaplan-Meier survival curves were created for complete vs partial revisions. RESULTS: There were 373 patients who underwent a total of 849 procedures. Of the 518 revision procedures, there were 163 (31.5%) complete shunt replacements and 323 partial shunt modifications. There were 283 subsequent failures after revision (54.6%), and the most common causes were proximal occlusion (38.5%), infection (9.9%), distal occlusion (8.5%), and disconnection (8.5%). There was no association between component revised and subsequent reason for failure. The use of distal slit catheters was associated with a higher rate of failure (61.4% vs 41.4%, P < .001). Complete revisions were less likely to undergo subsequent revision (46.6% vs 57.0%, P = .034). The average survival time was shorter for partial revisions; 3.9 vs 4.9 years ( P = .027). The Kaplan-Meier curve (Figure 1) showed a significant improvement in shunt survival for shunts replaced in their entirety ( P < .01). When the data were stratified by a shunt age of 2 years old (time implanted prior to revision), those with older shunts derived a greater survival advantage from complete shunt replacement ( P < .01). CONCLUSION: The complete replacement of a shunt at revision was associated with improved shunt survival. This benefit may be particularly important for shunts older than 2 years and those with distal slit catheters.